Finding an accuracy on legitimacy & reputation value based malicious node detection & removal scheme on cluster in MANETs - Sameera, D; C. Gayathri, V (International Journal of Engineering and Technology, 2018)
While Nodes forms networks dynamically & they doesnâ€™t have any central control infrastructure in mobile ad hoc networks thus routing becomes a significant issue. As packet forwarding is done by nodes itself there is increased possibility of packet dropping or DOS (denial of service) .so, the security in wireless networks became a challenging issue in MANET. For getting secure delivery of data we require efficient routing scheme, here is the proposal â€œFinding an Accuracy on Legitimacy & Reputation value Based Malicious Node Detection & Removal Scheme on Cluster in MANETsâ€ for detecting and removal of malicious nodes in a cluster. In this paper for a structured MANET, Network has number of clusters with number of nodes, each cluster has a cluster Head(CH), as packet forwarding done by nodes they need a node ID (including CH needs node ID) which is a prime number. Here to identify and use secure route between a source and a destination, every node need to maintain legitimacy value table(LVT) and reputation level table(RLT) in the network. The cluster head node Deny or Entail the malicious nodes from the identified route and select the most optimized route to a determined destination based on legitimacy value LV & reputation value RV.As proposed in existing system the reputation values calculation is not producing good accuracy and if we use the same calculation the efficiency will affect. So, we proposed the alternative solution for this and we identified new attack and here we are providing solution for this attack by finding accurate reputation value of Malicious Node (MN) by comparing in Reputation Level Table (RLT).Â Â